BUSINESS DEMOGRAPHY ISSUES AND EMPIRICAL RESEARCH ON DYNAMICS OF ENTERPRISES’ POPULATION IN POLAND - Ptak-Chmielewska, Aneta (Acta Scientiarum Polonorum. Oeconomia, 2011)
Business demography allows to measure the performance of enterprises in economy. The case of a country in transition such as Poland is a very interesting one. Despite joining the EU, there is still scarce and low quality data available. In fact, publications of the Central Statistical Office cover only firms registered in REGON (business register), which differs from the actual number of active enterprises. The number of active businesses represents about 60% of total registered fi rms. This study attempts to identify the most important qualitative and quantitative factors determining births and deaths of enterprises in the context of economic changes during the transition period. Due to limited access to additional surveys the analysis mainly focuses on the available data and covers descriptive analysis based on demographic indicators. Most spectacular results show that the dynamics of business population has been very low in recent years.